Load following mechanism and power flow algorithm under generator rotor angle control mode. Issue 7 (1st May 2016) - Wei, Qiang; Han, Xueshan; Guo, Weimin; Yang, Ming; Liu, Guojing
Abstract : Recently, a new strategy that controls generator rotor angle has appeared. The new control strategy can suppress inter‐area low‐frequency oscillations effectively without the help of any remote signal. It can also improve transient stability. This paper investigates the load balancing mechanism after rotor angle controllers are deployed. Analysis shows that the primary frequency control and automatic generation control currently used can be fulfilled in a new manner under this new control strategy. The generators can follow load demands quickly and precisely without the intervention of a dispatching centre. Consequently, the task of frequency control may be separated from the dispatching centre since the new control strategy is essentially decentralised and autonomous. Moreover, a load variation will be distributed to all generators that run in fix angle mode according to their distance from the load. Though power flow calculation is not needed during this process, it can be used to obtain generator outputs for any set of rotor angle aim values after loads change. Since generator rotor angle and the terminal bus voltage are given as inputs, the traditional Newton–Raphson method must be modified before it can be used. Those modifications and some extra steps with generator output limits are also given.